Respuesta :
Answer:
x = 1
Step-by-step explanation:
Given:
2(3x - 7) + 18 = 10
Solution:
Subtract 18 from both sides
2(3x - 7) + 18 = 10
- 18 -18
---------------------------
2 (3x-7) = -8
Now divide both sides by 2
2 (3x-7) -8
----------- = ------------
2 2
Simplify
3x - 7 = -4
Then add 7 to both sides
3x - 7 = -4
+ 7 +7
--------------------
3x = 3
Divide both sides by 3
3x 3
----------- = ------------
3 3
x = 1
Thus, Solution : x =1
~Lenvy~
Answer:
[tex]x = 1[/tex]
Step-by-step explanation:
Step 1
Simplify both sides of the equation
[tex]2(3x - 7) + 18 = 10[/tex]
Distribute
[tex](2)(3x) + (2)( - 7) + 18 = 10 \\ 6x + - 14 + 18 = 10[/tex]
Combine like terms
[tex](6x) + ( - 14 + 18) = 10[/tex]
[tex]6x + 4 = 10[/tex]
Step 2
Subtract 4 from both sides
[tex]6x + 4 - 4 = 10 - 4[/tex]
[tex]6x = 6[/tex]
Step 3
Divide both sides by 6
[tex] \frac{6x}{6} = \frac{6}{6} [/tex]
[tex]x = 1[/tex]